Balance function assessment and management - Barin, Kamran; Jacobson, Gary P.; Shepard, Neil T.; Barin, Kamran; Burkard, Robert F.; Janky, Kristen; McCaslin, Devin L. (San Diego c)
"The third edition of Balance Function Assessment and Management, the leading textbook on the subject, continues to comprehensively address the assessment and treatment of balance system impairments through contributions from top experts in the areas of dizziness and vertigo. Designed for use in graduate audiology programs and by practicing audiologists, this is also a valuable text for those in the fields of physical therapy, otolaryngology, and neurology"--
An historical perspective of the perception of vertigo and dizziness and vestibular medicine / Christopher K. Zalewski -- Ontogeny of the vestibular system and balance / Timothy A. Jones and Sherri M. Jones -- Practical anatomy and physiology of the ocular motor system / Scott D.Z. Eggers -- Practical anatomy and physiology of the vestibular system / Jamie M. Bogle and Robert Burkard -- Practical biomechanics and physiology of balance / Lewis M. Nashner -- Clinical neurophysiology of vestibular compensation / Kamran Barin -- The vertigo case history / Jay A. Gantz, Belinda C. Sinks, and Joel A. Goebel -- Assessing dizziness-related quality of life / Erin G. Piker, Gary P. Jacobson, and Craig W. Newman -- Bedside assessment of the vestibular system / Carrie W. Hoppes, Karen H. Lambert, and Devin L. McCaslin -- Eye movement recording and ocular motility testing / Neil T. Shepard, Michael C. Schubert, and Scott D. Z. Eggers -- Positional testing and treatment / Richard A. Clendaniel -- Caloric testing / Kamran Barin -- Rotational vestibular assessment / Christopher K. Zalewski -- The Video head impulse test (vHIT) / Ian S. Curthoys, Hamish G. MacDougall, Leigh A. McGarvie, Konrad P. Weber, David Szmulewicz, Leonardo Manzari, Ann M. Burgess, and G. Michael Halmagyi -- Computerized dynamic posturography : methodology & interpretations / Lewis M. Nashner and Neil T. Shepard -- Vestibular-evoked myogenic potentials (VEMPs) / Devin L. McCaslin and Gary P. Jacobson -- Electrocochleography (ECochG) / Paul R. Kileny and Devin L. McCaslin -- Pediatric vestibular testing / Kristen Janky and Neil T. Shepard -- Vestibular balance therapy for children / Jennifer B. Christy -- Medical management of vertigo that Is otologic in origin / Brian Neff and R. Mark Wiet -- Surgical management of vertigo that Is otologic in origin / R. Mark Wiet -- Neurologic origins of dizziness and vertigo / Joseph M. Furman and Susan L. Whitney -- Behavioral Factors in dizziness and vertigo / Jeffrey P. Staab -- Vestibular rehabilitation / Susan L. Whitney and Joseph M. Furman -- The Aging vestibular system : implications for rehabilitation / Dara Meldrum and Courtney D. Hall -- Topographical localization of vestibular system impairment / Gary P. Jacobson, Erin G. Piker, Richard A. Roberts, Devin L. McCaslin, and Nabih M. Ramadan -- Challenging cases / Neil T. Shepard.
Keywords: Audiology